Perancangan Sistem Pakar Mendiagnosa Penyakit Gigi Dan Mulut Menggunakan Metode Forward Chaining Berbasis Web Pada Tahap Pertama - Dahlan Haryanto; Dominius Sarumaha; Saiful Amir (CV. ITTC INDONESIA, 2025)
Expert systems have become an important tool in the medical field to assist in the disease diagnosis process. This research aims to design and develop a web-based expert system that uses the forward chaining method to diagnose dental and oral diseases. The forward chaining method was chosen because of its ability to make inferences from known facts towards a final decision or diagnosis. In this research, the author used the PHP and MySQL programming languages ​​for web development, and combined knowledge from dental experts to build an expert knowledge system base. The forward chaining method is implemented to link the symptoms entered by the user with possible dental and oral diseases. This expert system was tested using a dataset of relevant symptoms and diseases to test the accuracy of the resulting diagnosis. The test results show that this expert system is able to provide a diagnosis that matches the symptoms entered by the user with a high level of accuracy. Thus, it is hoped that this expert system can help in supporting the process of diagnosing dental and oral diseases efficiently and precisely.